2016
DOI: 10.1002/pon.4072
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and health‐related quality of life in AYA cancer survivors and controls

Abstract: Adolescent and young adult cancer survivors perceived a better quality of life than controls, especially those treated for haematological disorders or with a shorter off-treatment period. Future studies should aim to understand better this positive self-reported phenomenon, as well as investigating post-traumatic growth using qualitative narratives. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 59 publications
4
99
1
1
Order By: Relevance
“…However, if compared with a control group of healthy peers, HSCT‐healed patients, in this case both adolescents and young adults, reported a higher level of emotional well‐being, lower limitations related to this area, and less bodily pain. This was a quite new finding, because most studies showed more bodily pain (Berbis et al., ; Forinder et al., ), while emotional well‐being was usually comparable with norms (Schultz et al., ; Uderzo et al., ), even though there was found the same result in a recent Italian study on a cohort of childhood cancer survivors (who did not exclusively undergo HSCT) (Tremolada et al., ). HSCT experience was considered as potentially traumatic, even if off‐therapy patients could manifest also resilience in coping with painful life events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if compared with a control group of healthy peers, HSCT‐healed patients, in this case both adolescents and young adults, reported a higher level of emotional well‐being, lower limitations related to this area, and less bodily pain. This was a quite new finding, because most studies showed more bodily pain (Berbis et al., ; Forinder et al., ), while emotional well‐being was usually comparable with norms (Schultz et al., ; Uderzo et al., ), even though there was found the same result in a recent Italian study on a cohort of childhood cancer survivors (who did not exclusively undergo HSCT) (Tremolada et al., ). HSCT experience was considered as potentially traumatic, even if off‐therapy patients could manifest also resilience in coping with painful life events.…”
Section: Discussionmentioning
confidence: 99%
“…They showed lower educational attainment than their healthy peers (Berbis et al, 2013), especially those who received HSCT for haematological malignancies showed acute and chronic neurocognitive deficiencies (Shah et al, 2008) that could lead to more academic difficulties, resulting in less educational attainment (Freycon et al, 2014;Tremolada, Bonichini, Basso, & Pillon, 2016a).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The primary focus of this study was to investigate the relationships among PTG, loneliness, depression, social capital, and psychological resilience. In addition, three variables (age, gender, and household income) were included as potential confounding covariates given that they have been found to be related to these major variables in prior studies (Kaplan, Shema, & Leite, ; Tremolada, Bonichini, Basso, & Pillon, ; Vishnevsky, Cann, Calhoun, Tedeschi, & Demakis, ). For example, older age was found to be associated with greater PTG (Tremolada et al., ), women reported greater PTG (Vishnevsky et al., ), and higher income was found to be associated with lower psychological disorders (Lorant et al., ; Sareen, Afifi, McMillan, & Asmundson, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are long-term physiological and psychological sequelae of these treatments that may not manifest until paediatric survivors become adolescents [2,3], although other studies [4,5,6] suggest in these ex-patients a best psycho-social wellbeing than sane peers.…”
Section: Introductionmentioning
confidence: 99%